Eksplorasi Etnomatematika pada Kerajinan Gerabah dan Penerapannya dalam Pembelajaran Kalkulus Integral - Murti Kristiyani, Ika; Ernaningsih, Zeny (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
Ethnomathematics is a study that links culture with mathematics. Ethnomathematics can bridge students' learning difficulties in understanding mathematics. Ethnomathematics objects can be found around the environment, for example, pottery. This research aims to find mathematical elements in the typical Kulon Progo pottery culture so that it can be used to facilitate understanding of the concept of integral calculus, precisely the volume of a solid of revolution. This research is qualitative descriptive research with an ethnographic approach. The subjects of this research are pottery craftsmen in Bumirejo village, Lendah, Kulon Progo. Data collection was carried out by observation and interviews. Next, literature studies and data analysis were carried out to conclude. The research results found that pottery crafts in the form of mortars, jars, cauldrons, and flowerpots can be linked to learning the volume of rotating objects through rotating curves that resemble the shape of the pottery crafts. Hopefully, this research can help educators find fun learning alternatives and increase students' understanding of integral material. Keywords: ethnomathematics, pottery crafts, integral